Adolescents' Evaluation of Music Therapy in an Inpatient Psychiatric Unit: A Quality Improvement Project. Issue 1 (19th March 2015) - Preyde, Michele; Berends, Aimee; Parehk, Shrenik; Heintzman, John
Abstract: Consistent with Quality Improvement initiatives in health care and at Grand River Hospital, a quality assessment of the music therapy program at the Child & Adolescent Mental Health unit was conducted. Medical Students administered the surveys in which youth were asked to rate their experiences with music in general on a 4-point scale, and specifically with this music therapy program on a 5-point scale. Youth were also asked to provide their perceptions of aspects of the music therapy they considered helpful, challenging or needed attention. This report is based on the 72 youth who participated in music therapy and completed an anonymous evaluation survey. The mean age of participants was 14.88 (SD 1.77), 48 (67%) identified as female, and most 57/66 or 86% reported some type of anxiety. Youth indicated that the music therapy was helpful for elevating their mood, reducing anxiety and in socially interacting with others. Suggestions for quality improvement are offered.